Importance of Pragmatics and Semantics While Creating Advertising Slogans - Sherqulova Mahliyo Xasan qizi; Supervisor: Abduvahobova Mahina Azatovna (European Science Publishing, 2023)
The purpose of this paper is to explore the pragma-semantic features of advertising slogans. Advertising slogans are a critical component of marketing campaigns as they are meant to grab the attention of potential customers and create brand loyalty. These simple phrases or sentences contain hidden messages that convey the essence of a brand's proposition.
Keywords: slogan, pragmatics, marketing, semantics, brand, advertising.